Built of Wood and Turned to Soil: Perspectives of Research History and New Observations Concerning Finland’s Oldest Churches with Reference to Ristimäki in Ravattula. - Juha Ruohonen (Finland, 2022)
A few years ago, the remains of Finland’s oldest identified churches were still dated to the 1230s. Since the founding of parishes was placed in the early 13th century, these remains were associated with the period of ecclesiastical organization. In 2013, the well preserved stone foundation of a church presumably built already in the 12th century was excavated in Southwest Finland. Located in the middle of an inhumation cemetery, this building was associated with the ecclesiastical activities of the period of missionary activity in Finland and it may have been the church of a village or locality used by a community smaller than later parishes. Possibly dating from this period of the transition from the Iron Age to the Middle Ages are also two previously known foundations of belfries from two separate inhumation cemeteries. Because of very little information on the remains of early churches, the new finds discussed in this article provide considerable additions to our view of the early ecclesiastical culture of Finland.
New Sites, New Methods. Proceedings of the Finnish-Russian Archaeological Symposium, Helsinki, 19–21 November, 2014 (Iskos 21)